Tinjauan Yuridis Kerugian Negara Dalam Kerja Sama Operasional (KSO) Investasi Yang Dilakukan Oleh Yayasan Yang Didirikan Oleh BUMN (Studi Kasus Yayasan Bapelkes Krakatau Steel) - Faisal Anshari Dwana; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2022)
The foundation law allows foundations to open a business or invest 25% of the foundation's total wealth. When a foundation invests and suffers a loss, there are legal issues regarding liability for the loss of the foundation, especially foundations established by state-owned enterprises. This study is intended to unravel and analyze the position of the Foundation established by the BUMN (Bapelkes Krakatau Steel Foundation), the position of the Foundation's losses originating from operational cooperation (KSO) with other parties with losses to state finances and the Foundation's organs for losses arising from operational cooperation (KSO). ) by the foundation. This research is a normative legal research and is descriptive analytical. In this study, the legal approach (statute approach), conceptual approach (conceptual approach) is used. and the case approach. Secondary data as the main data were collected by using literature review techniques and analysis using normative-qualitative data analysis methods. As a legal entity, a foundation is an independent legal subject that has assets separate from the assets of its founder (separate legal entity). whether it is a foundation established by an individual or a BUMN, the legal status is the same, namely a legal entity, in other words every activity carried out by the foundation is the responsibility of the foundation itself. Therefore, when the Krakatau Steel Bapelkes Foundation entered into a KSO investment agreement and suffered losses, it also included state losses, but became the foundation's own losses. And the responsibility for the loss of the foundation is placed on the Trustees, Supervisors and Management of the Foundation if the loss occurs due to an error/omission, unless it can be proven that the loss did not occur due to an error or negligence due to his fault.